2020
DOI: 10.1177/1073191120976860
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Five-Factor Obsessive–Compulsive Inventory in a Mental Health Sample

Abstract: The Five-Factor Obsessive–Compulsive Inventory (FFOCI) is a recently developed measure of obsessive–compulsive personality disorder (OCPD) based on an established dimensional model of general personality, the five-factor model. The present study aimed to evaluate the construct validity of the FFOCI by examining its associations with both traditional and dimensional diagnostic models of OCPD. This study used an archival data set of mental health patients that employed a multimethod design. A total of 214 indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…OCPD was evaluated based on psychometric testing rather than clinical diagnosis. However, previous studies showed good validity of FFOCI in a mental health sample (Hall-Jones et al, 2021). Nevertheless, the observed effect sizes were large enough to be detected, and the limitations discussed did not preclude the identification of the most important and expected effects.…”
Section: Prevention and Treatmentmentioning
confidence: 81%
“…OCPD was evaluated based on psychometric testing rather than clinical diagnosis. However, previous studies showed good validity of FFOCI in a mental health sample (Hall-Jones et al, 2021). Nevertheless, the observed effect sizes were large enough to be detected, and the limitations discussed did not preclude the identification of the most important and expected effects.…”
Section: Prevention and Treatmentmentioning
confidence: 81%